Focus Group Discussion - Mir, Aized H. (World Bank, Washington, DC, 2014)
The Pakistan Infrastructure Implementation Capacity Assessment (PIICA) study was initiated in response to a specific request from the Government of Pakistan (GoP) to study the capacity of the local construction industry (client institutions, contractors and consultants) to deliver the planned infrastructure projects under the Medium Term Development Framework (MTDF). The objectives of the focus group discussions were to: (i) ensure active participation and ownership of stakeholders in the study; (ii) obtain concurrence on the framework for the study and the technical analyses to be carried out; and (iii) obtain feedback and comments on findings and develop consensus on the way forward. Focus group discussions helped identify the broad thematic areas and the issues which should be researched. The discussion provided a framework for preparation of a detailed questionnaire to be used for ascertaining stakeholders' perceptions about the industry and to solicit their comments and suggestions. The focus group also identified the need for carrying out separate technical analyses and emphasized that case studies of various projects should be prepared. The focus group discussions validated the results obtained from the perceptions surveys and the technical analyses and the stakeholders concurred with the complex issues and challenges faced by the construction industry. While valuable suggestions were provided in the focus group discussions which can remove a number of constraints faced by the industry, there were no solutions offered which could be implemented to provide increased capacity over the short-term as the systematic weaknesses in the business environment, the lack of adequately skilled human resource (HR), lack of client agencies capacity, lack of financing, and credit available to the industry and other constraints cannot be addressed within an immediate or short-term time frame clearly, besides taking measures to develop the local construction industry, innovative methods of procurement, and delivery mechanisms will need to be thought of in order to meet all of the MTDF infrastructure development goals.